(untitled) (Journal of the College of Basic Education, 2024)
Migration and displacement are considered one of the biggest humanitarian challenges of our time because people are displaced for various reasons, including natural ones due to climate change and natural disasters or non-human reasons such as conflict, violence and food insecurity. Some may move voluntarily for work or education, while others are forced to flee and be forcibly displaced from their homes to safer and more stable places. This research paper addressed the displaced in the southern governorates of Iraq, namely (Basra Governorate, Maysan Governorate and Dhi Qar Governorate). It came in five sections, the first of which includes the theoretical framework of the problem, hypothesis, study objective and the boundaries of the study area, while the second section dealt with the types of displacement and demographic characteristics of the population of the study area. The third section dealt with the geographical distribution of the displaced, while the fourth section showed the most important effects resulting from displacement, and finally the conclusions and recommendations. The research found that the total number of displaced families in the research area was (2455) families, and the highest percentage of displaced families was in Nasiriyah Governorate (63.3%) Displaced families, followed by Maysan Governorate, which ranked second with a percentage of (28.2%) displaced families, while Basra Governorate came in third place with a percentage of (8.5) displaced families. The trends of migration or displacement in Dhi Qar and Basra Governorates were internal and external, while in Maysan Governorate, displacement was between the districts of the governorate itself. The natural factor was the most important factor and the main cause of the displacement of the population from the research area, such as drought and the decline in the level of surface water due to the construction of dams and the change in the course of the tributaries that fed the Tigris and Euphrates Rivers, most of which are located outside Iraq, which caused a decrease in water scarcity, in addition to the rise in temperatures, which contributed to increased evaporation, deterioration of the vegetation cover and the shrinkage of agricultural areas. Other reasons for displacement were caused by tribal tensions and conflicts in the research area, which affected the most vulnerable and fragile families and their displacement to the districts and districts of other governorates.